Bringing Artificial Intelligence (AI) in Teaching and Learning Process - Bastomi Bastomi; Ahmad Zarkasyi Mujahid; Asmuni Asmuni; Ahmad Sibron; Mia Audina; Kasinyo Harto (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Artificial Intelligence (AI) has emerged as a pivotal technology significantly impacting various sectors, including education. In the context of learning, AI holds the potential to improve personalization, automate assessments, and enhance learning analytics. However, in Islamic education, AI's implementation must align with the values of Islamic educational management and supervision. This study analyzes the application of AI in Indonesia's teaching and learning process while evaluating its benefits, challenges, and relevance to Islamic educational supervision. Using a literature review methodology, this study explores the role of AI in enhancing educational quality, particularly through personalized learning and administrative efficiency. Findings indicate that AI can assist supervisors in monitoring educational processes to ensure they are in line with Islamic values, such as justice, transparency, and character building. However, challenges such as technological infrastructure, digital literacy, data privacy, and algorithm bias remain significant. The study concludes that collaboration between the government, educational institutions, and supervisors is essential to develop infrastructure, train educators, and create policies that protect student privacy and uphold Islamic values. Future research should delve deeper into how Islamic educational supervision can optimize AI implementation in diverse educational settings.